Relevant organic architecture - Malakhov, Sergey; Repina, Evgeniya (project baikal, 2022)
In the context of post-epidemic revision of work-home-center relationships and the growth of online communication there is no need to assert the exceptional importance of multistory residential complexes located in the closest accessibility to functional subsystems of the metropolis. The return to medium-rise housing within compact localities integrated into the natural or historical environment is becoming a kind of reincarnation of the philosophy and language of organic architecture. The expansion of this trend will be accompanied by an increased demand for the activities of the architect, the master of organic form. The article considers the method of work based on invariant codes of F. L. Wright’s organic architecture, key architectural criteria of compact locality and predicted correction of the method due to spontaneous transformations of initial design solutions.
Keywords: crisis of urban environment; compact locality-polises; master architect; master’s basic competences; integral form; tactile modeling; participation